Mystery history of a Pirate Galleon - Finney, Fred; Nang ChanYeema (New York, USA Copper Beech Books, 1996)
Describes life aboard a pirate ship. Includes games, puzzles, and mazes.
Keywords: Juvenile Nonfiction